The Application of Berkovich nanoindenter to the study of interfacial transition zone in concretes containing fly-ash - Golewski, Grzegorz (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper presents the results of nanohardness (HB) in the Interfacial Transition Zones (ITZ) of concretes with the addition of 0, 20 and 30% siliceous fly ashes (FA). A compact platform CSM Instruments was used in the testing. An area in the ITZ of coarse aggregates with paste was analysed in the five measurement points during the experiments, i.e. at the distance of: 5, 25, 50, 100 and 150 µm from the grain boundary. The indents in concrete were create by Berkovich indenter using DSI technique. Analysis of the results revealed that the 20% additive of FA causes a few percent increase in nanohardness, while 30% FA additive leads to between ten and twenty percent drop of HB. On the basis of nanohardness distributions in particular concretes, it was found that the most heterogeneous one is the ITZ zone within the distance of 25µm from the aggregate grain.